Web-Based File Sharing System: A Case Study of Kabale University. - Akandinda, Abraham (Kabale University, 2023)
The aim of this research study was to design and implement a distributed web-based file sharing and access control system that would provide users with an online storage and sharing platform and at the same time, with sufficient security means. The study was guided with three specific objectives and these included; studying and analyzing the current file sharing system used at Kabale University, developing a Web-based file sharing system for Kabale University, and to test and validate the proposed Web-based file sharing system. The general strategy of this study outlined the use of the Structured System Analysis and Design Methodology (SSADM) in the system's development life cycle. This model divides the system into two phases. System development tools used included; PHP Scripting Language as the server-side language and MySQL as the Database for the system. With this system, users can access their files in the server securely and concurrently. Sharing files is also protected by access control. Security, user - friendly and cross platform capability are the main purposes of the new Web-based File Sharing System. Future File Sharing systems should be computer-based, multimedia systems capable of including free text, high-resolution images, sound, full-motion video, and elaborate coding schemes. Such systems offer access (availability, convenience, speed, reliability, and ease of use), quality, security, flexibility, connectivity, and efficiency. In addition, future web-based file sharing should provide new functions through links to other databases and decision support tools. This will re-shape service delivery and improve technology to enhance on line sharing of data.